A Map of Nationalism Message on Twitter/X Users in Indonesia - Sari, Dewi Kartika; Herwandito, Seto (Universitas Muhammadiyah Yogyakarta, 2025)
This research was motivated by the global rise in social media usage, which has introduced and disseminated universal values. In Indonesia, nationalism is increasingly challenged by the influx of global information through platforms like social media. The study aims to map the production of nationalism-related messages posted by Twitter/X users in Indonesia. A mixed-methods approach—combining both quantitative and qualitative techniques—was employed to analyze how nationalism messages were produced. The analysis focused on public participation, particularly in relation to gender, the geographic location of tweets, sentiment and emotion analysis, as well as the most commonly used hashtags and keywords on August 17, 2024. The findings reveal that nationalism messages from Indonesian Twitter/X users are organically generated by the public, with the predominant theme being expressions of Independence Day congratulations. The most influential actor in the message network was the account @aingriwehuy. In conclusion, public participation in celebrating Indonesia’s Independence Day was evident across all regions of the country and involved both female and male users. The messages were largely characterized by positive emotions and sentiments. Keywords: map; message; nationalism, Twitter (X); Indonesia